Opportunities and issues for biometry in a rapidly changing environment - Nokoe, S.; Ojurongbe, T.; Bamiduro, T. (2000)
Changes in the environment demand changes in the practice of biometry. Classical on-station researcher-managed trials and associated assumptions are restricted in scope, and are getting old-&shinned. Indeed on-station trials are gradually giving way In on-farm farmer participatory trials, which incorporate the interaction nature of the environment and other farmer social and economic circumstances. Environmental issues that are being addressed goes beyond designs and conventional estimation of the effects of treatments. For instance, evaluation of 'fisheries' trials incorporates and analyses fur possible effect and sources of efficient (If location is in an oil-producing area), and water pollution. Crop trials involving the use of wood stakes (as in yam studies) or livestock grazing studies must regularly analyze the effects on furriest and soil degradation. Tools for such estimations need In be developed jointly by the environmentalist and statistician.